Effect of using two packing Technic on Hardness of two dental acrylic resin - nasser, Najim (Iraqi National Journal of Nursing Specialties, 2012)
Objective: the aim of this study is to invest age and determine the effect of using (2) packing technique (conventional and new tension technique) on hardness of (2) types of heat cure acrylic resin which are (Ivoclar and Qual dental type). Methodology : this study was intended the using of two types of heat cure acrylic (IVoclar and Qual dental type) which are used in construction of complete denture which packed in two different packing technique (conventional and new tension technique) and accomplished by using a total of (40) specimens in diameter of ( 2mm thickness, 2 cm length and 1 cm width) . This specimens were sectioned and subdivide into (4) group each (10) specimens for one group , then signed as (A, Al B , B 1) according to the method of technique and type of acrylic that used . The hardness of the specimens were measured by shore hardness test in technology university, Baghdad. Results: this study revealed that the type of acrylic which packed by new tension technic had less effect by hardness in compared with conventional packing technic, the result also showed that the type of acrylic resin have a little effect on hardness of the two types, and also it show highly mean value of hardness was indicate in Qual dental type in conventional technique, while the least mean value of hardness showed in Ivoclar type in new tension technique. Recommendations : this study has been conducted as a preliminary for future studies to give a sit of about the effect of hardness on other types of commercial heat acrylic resin that used in construction of prosthodontics restoration and dented prosthesis, it necessary to evaluate the hardness of any material used in construction of denture bases , it is suggested to under take a farther studies about using advance technique and better apparatus and device in packing the acrylic material and measured the value of hardness and its effect on this material.